Observation of quasi-coherent fluctuations in the Globus-M spherical tokamak. (29th July 2021) - Yashin, A.Yu.; Bulanin, V.V.; Gusev, V.K.; Kiselev, E.O.; Kurskiev, G.S.; Minaev, V.B.; Patrov, M.I.; Petrov, A.V.; Petrov, Yu.V.; Ponomarenko, A.M.; Shchegolev, P.B.
Abstract: The first results of studies of quasi-coherent fluctuations (QCFs) in the spherical Globus-M tokamak are presented. QCFs were observed as oscillations of the Doppler backscattering (DBS) amplitude. These oscillations were not detected in the spectra of the complex signal of the quadrature detector, the shift of which determines the plasma rotation velocity. The multi-frequency DBS scheme allowed us to determine the region of existence of the QCFs ( ρ = 0.6–0.7). Bicoherence analysis of the backscattered power demonstrates a nonlinear interaction between broadband turbulence and QCFs. The detected QC fluctuations were interpreted as relatively long-wave oscillations that influence the backscattering on shorter-wave oscillations.